Method of partition of load between servers of system the internet voting - Чуприн, Володимир Михайлович; Антонов, Веніамін Валерійович; Комарницький, Олег Олександрович (Ukrainian Information Security Research Journal, 2019)
The method of optimal adaptive distribution of stream of queries of electors is offered between the servers of the system internet-voting, that produce the automatic search of ip-address of servers of electoral districts. For basis the chart of access of electors is taken to servers of electoral districts, that in detail is considered in [3]. For automation of search the line of the specialized servers of search of addresses (SA) is used in this chart. Programmatic facilities of these servers in reply to the queries of electors in real time execute procedure of search in accordance with any of the known methods of search. The found values of ір-addresses are sent on the terminal knots of initiators of queries.Along with the line of servers of SA that functions imultaneously and independent of each other, in complement of equipment of the controlled from distance secret voting system the additional element of queries is entered also. It is manager (server of translation of queries), that in real time must execute adaptive distribution of stream of queries between the servers of SA with that to provide the even loading of these servers in the conditions of the unforecast splashes (pulsations) of stream of queries during voting. Realization of method allows to perfect technology of the controlled from distance access of electors to the resources of the system internet-voting. In particular, to provide the even loading of server equipment in the conditions of the unforecast pulsations of traffic of electors, and also possibility of support of acceptable level of quality of treatment of these queries (in particular, support of acceptable value of mean time of expectation in a turn on maintenance of queries) with the use of the least of server equipment. Parameters of this technology are certainly as a result of decision of corresponding optimization task that will realize method of the dynamic programming of Bellman.